Mammographic breast parenchymal patterns in Thai women with breast cancers - Bunjunwetwat, Darunee; Dumrongpisutikul, Netsiri (Chulalongkorn Medical Journal, 2023)
Introduction : Dense breast parenchyma are reported as increasing risk of breast cancer from the previously study. The dense breasts have a role to consider additional MRI to the screening mammogram for early detection in women with moderately increased breast cancer risk. Objective : To assess breast parenchymal patterns of Thai women with breast cancers. Setting : King Chulalongkorn Memorial Hospital Research design : A retrospective study. Patients : Thai women who had verified of breast cancers and had bilateral mammography in King Chulalongkorn Memorial Hospital. Methods : Seventy two Thai women with breast cancers were retrospectively reviewed for breast parenchymal patterns from the latest mammography before surgery by a skilled breast radiologist. The breast parenchymal patterns were classified according to Wolfe’s classification (N1, P1, P2 and Dy). Results : The mean age value of 72 Thai women with breast cancers is 50 years (age range 32 - 75 years). The breast parenchymal patterns of these women were 2 cases as type N1 (3%), 12 cases as type P1 (17%), 26 cases as type P2 (36%) and 32 cases as type DY (44%). The P2 and Dy breast parenchymal patterns are majority in 3 age-groups; 30 - 39 years, 40 - 49 years and 50 - 59 years. The most frequent cancer type is invasive ductal carcinoma (66 cases, 91.7%). Conclusions : Type P2 and DY represented dense breast were the most prevalent mammographic breast parenchymal patterns in Thai women with breast cancers.